Análisis de la publicidad en youtube como medio para incentivar el desarrollo cultural de la juventud del cantón Babahoyo - Gomez Flores, Gabriel Alejandro (2020)
The purpose of this research work is to analyze the behavior of both pedestrians and conduits in the city of Babahoyo, and as the lack of publicity on road education affects, within this project it was necessary to collect theoretical information, in order to understand certain Important parameters within the world of digital advertising through YouTube and its communicational impact. In this way, it can be understood that advertising through YouTube is extremely important as it generates information both as entertainment and educational. To this end, the context where the research technique was applied, such as the survey of the students of the Eighth semester of Social Communication, was analyzed, gave their insights on how important it is to raise awareness among young people about the importance of road education, traffic laws in the city of Babahoyo.